Changes in Phase Behavior from the Substitution of Ethylene Oxide with Carbon Dioxide in the Head Group of Nonionic Surfactants. Issue 3 (30th December 2019) - Spiering, Vivian J.; Ciapetti, Aurora; Lima, Michelle Tupinamba; Hayward, Dominic W.; Noirez, Laurence; Appavou, Marie‐Sousai; Schomäcker, Reinhard; Gradzielski, Michael
Abstract: Nonionic ethylene oxide (EO)‐based surfactants are widely employed in commercial applications and normally form gel‐like liquid crystalline phases at higher concentrations, rendering their handling under such conditions difficult. By incorporating CO2 units in their hydrophilic head groups, the consumption of the petrochemical EO was reduced, and the tendency to form liquid crystals was suppressed completely. This surprising behavior was characterized by rheology and studied with respect to its structural origin by means of small‐angle neutron scattering (SANS). These experiments showed a strongly reduced repulsive interaction between the micellar aggregates, attributed to a reduced hydration and enhanced interpenetration of the head groups owing to the presence of the CO2 units. In addition, with increasing CO2 content the surfactants became more efficient and effective with respect to their surface activity. These findings are important because the renewable resource CO2 is used, and the CO2 ‐containing surfactants allow handling at very high concentrations, an aspect of enormous practical importance. Abstract : Pleasantly sur‐phased : By incorporating CO2 units in the hydrophilic head groups of nonionic surfactants, the tendency to form liquid crystalline phases is suppressed completely, and their viscosity in water remains low up to the highest concentrations. This surprising behavior is characterized by rheology and explained with respect to its structural origin by means of small‐angle neutron scattering (SANS).